Associations of marital violence with different forms of contraception: Cross‐sectional findings from South Asia. (25th March 2015) - Raj, Anita; McDougal, Lotus; Reed, Elizabeth; Silverman, Jay G.
Abstract: Objective: To assess associations between marital violence and type of contraception among women in South Asia. Methods: Cross‐sectional analyses were conducted using marital violence data collected during the most recent Demographic and Health Surveys from Bangladesh (n = 3665), India (n = 56 357), and Nepal (n = 3037). Data were pooled to assess associations of marital violence (physical or sexual) with modern contraception use (current spacing or sterilization). Results: Sexual marital violence was associated with both modern spacing contraception (adjusted odds ratio [AOR] 1.30; 95% confidence interval [CI], 1.13–1.49) and sterilization (AOR 0.79; 95% CI, 0.70–0.88). Sexual violence was reported more often by pill users (9.8% vs 5.5% for non‐users) but less often by condom users (4.5% vs 5.8% for non‐users). Conclusion: Sexual marital violence might increase use of contraception that need not require husband involvement (pill) but decrease use of methods that require his cooperation (condom) or support for mobility, funds, or time (sterilization).